Integration of Total Quality Management (TQM) in Business Practice: A Bibliometric Analysis - Susiati, Devi; Judijanto, Loso; Suprayitno, Degdo; Suarni, Ertati (Westscience Press, 2024)
This research methodology outlines the systematic approach to conducting a bibliometric analysis on the integration of Total Quality Management (TQM) in business practice. TQM is a widely studied and implemented management philosophy aimed at improving organizational processes and enhancing overall performance. Through bibliometric analysis, this study seeks to provide a comprehensive understanding of the existing literature landscape, key research trends, influential authors, and thematic clusters related to TQM integration in business practice. The methodology covers the selection of databases, search strategy formulation, inclusion and exclusion criteria, data extraction, analysis techniques, and interpretation methods. By employing rigorous bibliometric techniques, this research aims to contribute to the advancement of knowledge in the field of TQM and its practical implications for businesses.